2018
DOI: 10.1177/1077801218755975
|View full text |Cite
|
Sign up to set email alerts
|

What Constitutes Rape? The Effect of Marital Status and Type of Sexual Act on Perceptions of Rape Scenarios

Abstract: Many people believe that rape is always perpetrated by a stranger and involves vaginal intercourse. To clarify perceptions of rape that do not follow traditional beliefs, participants were presented with a vignette that described a rape in which the marital status and sexual act were manipulated. Participants were then asked to assess the incident's severity and the victim's responsibility. Results indicated that there was no difference in perceptions between vignettes based on marital status. However, rapes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Marital rape is recognized as a significant public health concern worldwide that has existed for a long time and has remained mostly hidden and understudied (Chhabra, Namgyal, & Tyag, 2014;Dude, 2011;Finkelhor & Yllo, 1985;Russell, 1982;Yllo & Torres, 2016). The prevalence of marital rape remains high and continues to have severe consequences for women's health and society (Adams-Clark & Chrisler, 2018;Ellsberg et al, 2008). Despite its severity and consequences, marital rape has received little attention in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Marital rape is recognized as a significant public health concern worldwide that has existed for a long time and has remained mostly hidden and understudied (Chhabra, Namgyal, & Tyag, 2014;Dude, 2011;Finkelhor & Yllo, 1985;Russell, 1982;Yllo & Torres, 2016). The prevalence of marital rape remains high and continues to have severe consequences for women's health and society (Adams-Clark & Chrisler, 2018;Ellsberg et al, 2008). Despite its severity and consequences, marital rape has received little attention in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these perceptions of intimate partner sexual victimization, prior abuse history and individual participant differences (such as gender and marital status) are important to explore. Overall, it seems to be the case that as the intimacy of offender–victim relationships increase, the perceived severity of rape decreases (Adams-Clark & Chrisler, 2018; Ben-David & Schneider, 2005; Martin et al, 2007). The existing literature (e.g., Ferro et al, 2008; Monson et al, 2000) has focused on perceptions of forced rape involving intimate partners compared with non-intimate partners.…”
Section: Cultural Myths Of Rapementioning
confidence: 99%
“…Perceptions of rape seem to vary based on several factors, including the victim’s gender (Smith et al, 1988; Sommer et al, 2016), the context of the assault (e.g., date rape compared with intimate partner rape, victim dress; Kirkwood & Cecil, 2001; Simonson & Subich, 1999), as well as the gender of the perceiver (Adams-Clark & Chrisler, 2018; Monson et al, 2000). For instance, previous research has found that females tend to exhibit more pro-victim judgments than do their male counterparts (Ferro et al, 2008; Lynch et al, 2017, 2019; Monson et al, 2000).…”
Section: Cultural Myths Of Rapementioning
confidence: 99%
“…According to the United Nations Fund, in India, more than two-thirds of married women between age group 15 and 49 years are exposed to forced sex, rape and physical violence (Jiloha, 2015). It is very ambiguous that rape between unmarried partners is seen differently than the rape between married partners, even though they share similar relationships in both the conditions (Adams-Clark & Chrisler, 2018). Rape rate in India as per reported cases is 1.80 (World Population Review, 2020).…”
Section: Sexual Violencementioning
confidence: 99%